The Feasibility of Antioxidants Avoiding Oxidative Damages from Reactive Oxygen Species in Cryopreservation - Liu, Xiangjian; Xu, Yiming; Liu, Fenglin; Pan, Yuxin; Miao, Lu; Zhu, Qubo; Tan, Songwen (Frontiers in Chemistry, 2021)
Cryopreservation prolongs the storage time of cells and plays an important role in modern biology, agriculture, plant science and medicine. During cryopreservation, cells may suffer many damages, such as osmotic dehydration, large ice puncture and oxidative damages from reactive oxygen species (ROS). Classic cryoprotectants (CPAs) are failing to dispose of ROS, while antioxidants can regulate oxidative stress and turn ROS into harmless materials. The combination of antioxidants and CPAs can improve the efficiency of cryopreservation while negative results may occur by misuse of antioxidants. This paper discussed the feasibility of antioxidants in cryopreservation.